Antioxidant properties of dried ginger (Zingiber officinale Roscoe) var. Bentong - Mustafa, Iswaibah; Chin, Nyuk Ling (Multidisciplinary Digital Publishing Institute, 2022)
Ginger (Zingiber officinale Roscoe) is a popular culinary herb used in the Eastern culture. The essential cultivar of the Zingiber genus is rich in antioxidants and is crucial in the fight against oxidative stress-related diseases. The antioxidant properties of dried ginger were evaluated and compared for their efficacy from different drying processes (sun-, oven-, vacuum- and freeze-drying) and using three extraction solvents: hot water, aqueous ethanol (80%, v/v) and ethanol. The drying process demonstrated a positive effect on the antioxidant activities of ginger. A significant difference (p < 0.05) was observed in the extracting ability of each solvent. Sun-dried ginger extracted with ethanol performed better than the fresh ginger extract in the form of increased yield (3.04-fold), TFC values (12.25-fold), reducing power (FRAP) (15.35-fold), total antioxidant activity (TAA) (6.82-fold) and inhibition of ABTS•+ radical cation (3.51-fold) and DPPH• radical (95%). Meanwhile, freeze-dried aqueous ginger extracts demonstrated significantly higher TPC (1.66-fold), TFC (3.71-fold), FRAP (3.26-fold), TAA (2.97-fold), ABTS•+ scavenging activity (1.48-fold) and DPPH• radical inhibition (77%), compared to fresh ginger extracts. In addition, it was found that ethanol was significantly superior to aqueous ethanol in phenolic content recovery, despite the lower yield. Furthermore, ethanol ginger extracts exhibited higher antioxidant activity than aqueous ethanol extracts. On the other hand, hot water was the least potent solvent for extraction. In summary, there was an excellent correlation between TPC, TFC and antioxidant activity. Sun-drying is the most desirable method for preserving and enhancing ginger quality due to its cost effectiveness and bioactive compound efficacy.